Indonesia IndonesiaPENGEMBANGAN MEDIA PEMBELAJARAN AUGMENTED REALITY PADA MATERI PERANGKAT KERAS KOMPUTER: Indonesia - Dion, Muhammad; Mulyono, Heri; Kurniawan, Haris (Information Technology Education Department, 2025)
The purpose of this study was to produce Augmented Reality learning media there is a valid XI DKV class computer hardware material. To produce Augmented Reality learning media there is a practical XI DKV class computer hardware material. This research method uses the Research and Development (R&D) method with the ADDIE development model. The subjects of this study consisted of 3 media validation people, 2 material validity people, 2 teacher practicality people and 17 student practicality people. The results of this study showed the average value of the media validation test by the validator was 85.25% with a very valid category while the material validation was 95.75% with a very valid category. The teacher's practicality test was 96.33% with a very practical category while the practicality of the XI DKV class students was obtained at 93.01%. Augmented Reality learning media there is computer hardware material worth using as learning. improving the quality of learning, with the use of media that is more interactive and efficient for teachers and students, and able to increase student learning motivation.